Resíduos de pesticidas em mel de Apis Mellifera produzidos na microregião de Toledo - Paraná - Model, Kathleen Jenifer (2021)
Brazil stands out in national and international honey production, due to its rich floristic diversity and year-round favorable climate. Nationally, the South and Northeast regions are the largest producers, accounting for roughly 70% of total honey production. However, this scenario is under constant threat, because bee’s colonies have been collapsing, and the main villain has been pesticides. Among them are systemic insecticides such as imidacloprid and fipronil, which are widely used, mainly in soybean and corn crops. Therefore, the aim of this study was to assess the quality of honey in terms of fipronil and imidacloprid concentrations in the microregion of Toledo, Paraná, and to relate the concentrations to the use and occupation of foraging areas in the collected apiaries. Samples were collected in December 2019, and the proposed method for extraction and quantification was first validated in selected chromatographic systems. Following that, the samples went through a solid-phase extraction process coupled to a cartridge for later reading in chromatography. The method validation parameters were satisfactory. The linearity presented R2 ≥ 0.99 for both compounds. With LD 0.007 and LQ 0.005 µg ml–1, recovery for imidacloprid was 92.28%, while recovery for fipronil was 118.32%, with LD 0.003 and LQ 0.005 µg ml–1. In terms of representativeness, imidacloprid concentrations ranged from up to 2.07 µg ml – 1 in 41.34% of the samples, while fipronil contamination ranged from up to 0.0675 µg ml-1 in 87.8% of the samples. In the year 2019, the highest concentrations of these compounds coincided with land use in bee foraging areas and the use of these compounds in arable areas. Overall, the microregion represented 49.83% of the total area in terms of arable areas, with Group 1 accounting for 70.96, Group 2 for 56.99%, which had the highest concentrations of fipronil, and Group 3 accounting for 41.32% of the total area with agricultural activity, which had the highest concentrations of Imidacloprid in its comprehensive region. Itaipulândia and Missal, which together marketed 18804.76 kg of imidacloprid for various cultures, stood out in terms of commercialization of the insecticide. Terra Roxa and Guaíra, which together sold 1,822 kg of fipronil, and Marechal Cândido Rondon, to the southwest, sold 864 kg of the compound. This data matches the concentration mapping in the microregion under study. In general, all concentrations of both compounds found, even those considered low for the research, exceeded the international bodies’ Maximum Residue Limits. As a result, it can be concluded that the use of fipronil and imidacloprid has an impact on the honey quality as well as the entire beekeeping system in the region. So, if we do not achieve a balance in the use of pesticides while respecting the extent of bee foraging, we will not only jeopardize beekeeping activity in terms of productivity and honey quality, but we will also cause a decline in bee colonies, resulting in an environmental collapse that will affect the entire pollination system, as well as the sustainability and balance of the ecosystem involved.